Detailed Radio View on Two Stellar Explosions and Their Host Galaxy: XRF 080109/SN 2008D and SN 2007uy in NGC 2770 - van der Horst, A.; Kamble, A.; Paragi, Z.; Sage, L.; Pal, S.; Taylor, G.; Kouveliotou, C.; Granot, J.; Ramirez-Ruiz, E.; Ishwara-Chandra, C.; Oosterloo, T.; Wijers, R.; et al. (Institute of Physics Publishing, Inc., 2011)
The galaxy NGC 2770 hosted two core-collapse supernova (SN) explosions, SN 2008D and SN 2007uy, within10 days of each other and 9 years after the first SN of the same type, SN 1999eh, was found in that galaxy.In particular, SN 2008D attracted a lot of attention due to the detection of an X-ray outburst, which has beenhypothesized to be caused by either a (mildly) relativistic jet or the SN shock breakout. We present an extensivestudy of the radio emission from SN 2008D and SN 2007uy: flux measurements with the Westerbork SynthesisRadio Telescope and theGiant MetrewaveRadio Telescope, covering~600 days with observing frequencies rangingfrom 325 MHz to 8.4 GHz. The results of two epochs of global Very Long Baseline Interferometry observationsare also discussed. We have examined the molecular gas in the host galaxy NGC 2770 with the Arizona RadioObservatory 12 m telescope, and present the implications of our observations for the star formation and seeminglyhigh SN rate in this galaxy. Furthermore, we discuss the near-future observing possibilities of the two SNe andtheir host galaxy at low radio frequencies with the Low Frequency Array.